AB0548 Cardiac Involvement in Patients with Antiphospholipid Syndrome: A Case Series with a Long-Term Follow-Up. (9th June 2015) - Martínez-Vidal, A.I.; Vázquez-Triñanes, C.; Villaverde-Άlvarez, I.; Rodríguez-Gόmez, A.; Soto-Peleteiro, A.; Argibay, A.; Freire, M.; Sopeña, B.; Rivera, A.
Abstract : Background: Antiphospholipid syndrome (APS) is a multisystem disease, and the heart may be affected from 10 to 50% in some series [1, 2]. Heart valve lesions are the most frequent manifestations. Coronary arteries and myocardium may be also affected. Other findings include chronic thromboembolic pulmonary hypertension and accelerated atherosclerosis. Some studies have suggested a higher incidence of cardiac involvement in patients with secondary APS or those with higher titers of antiphospholipid antibodies. However, cardiac involvement in APS are not yet well known because there are few published series and most of them have a short-term follow-up. Objectives: The aim of our study was to determine the prevalence and the type of cardiac involvement in patients with APS. Also, risk markers of cardiac involvement in these patients were attempted to identify. Methods: A case series of patients with APS diagnosed and followed for a long period in a specific unit of Thrombosis and Vasculitis was conducted. Clinical and laboratory data were collected in a retrospective manner. To attempt to identify risk markers of cardiac involvement, patients with cardiac manifestations were compared with patients without heart involvement. Chi2 and t-student were used, using the statistical package SPSS18.0. Results: 32 patients with APS were included, 21 (66%) female, mean age 64.3±16.44 years [range 34-84], with a mean follow-up of 9.2 years (median 7 years). 8 patients (25%) had a secondary APS: 3 SLE, 2 Sjögren's syndrome, 1 rheumatoid arthritis, 1 systemic sclerosis and 1 demyelinating disease. 4 (13%) were pure obstetric APS, 9 (28%) had an arterial thrombosis, 9 (28%) had a venous thrombosis and 10 (31%) had mixed events (arterial, venous, and obstetric). 23 (72%) of patients had a cardiovascular risk factor (hypertension, dyslipidemia, type 2 DM). 19 patients of 32 with APS (59%) had cardiac involvement. 15 patients (79%) had valve disease (7 mitral valve, 3 aortic valve and 5 both mitral and aortic valves), and 8 (26%) had a coronary ischemic event. No patients had pulmonary hypertension. The comparison results between the two groups are shown in the following table . Conclusions: More than half of patients with APS had cardiac involvement. Heart valve disease was the most frequent manifestation, almost always mitral valve. No patients had pulmonary hypertension. The only risk marker of cardiac involvement in our series was the age; patients with cardiac involvement were 10 years older on average. References: Cardiac involvement in the antiphospholipid syndrome. Tenedios F et al. Lupus 2005. 14(9):691-696. Cardiac manifestations in antiphospholipid syndrome. Soltész P et al. Autoimmun Rev. 2007;6(6):379-86. Disclosure of Interest: None declared